Peran Kearifan Lokal Sunda Wiwitan dalam Membentuk Karakter Masyarakat Di Kampung Pasir Garut - Wahyuni, Dede Sri; Maulana, Ana (Universitas Muhammadiyah Ponorogo, 2026)
This article discusses the role of Sunda Wiwitan local wisdom in shaping the character of the community in Kampung Pasir, Garut Regency. The main issue raised is how the traditional values, beliefs, and social practices of the Sunda Wiwitan community contribute to the formation of the character of the indigenous community based on the values of pancasila, tolerance, togetherness, and legal awareness. This study uses a qualitative approach with descriptive methods, which aims to describe and understand in depth the role of Sunda Wiwitan local wisdom in shaping the character of the community as citizens. Data collection was conducted through interviews with traditional leaders and local community members, observations of the socio-cultural environment, and documentation of applicable traditions and customary rules. The research findings indicate that Sunda Wiwitan teachings encompass values of compassion, etiquette, teaching fellow human beings, environmental sustainability, and adherence to customary law and government. Thes values are embodied in traditions of birth, marriage and death, as well as traditional educational activities such as the Taman Atikan (a traditional garden) which plays a vital role in fostering the younger generation. The study concludes that Sunda Wiwitan local wisdom is strongly relevant in shaping the character of the community as ethical, tolerant, and responsible citizens amidst the challenges of modernization.